2013
DOI: 10.1021/ja4106122
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Hydrogen Bonds and n→π* Interactions in Proteins

Abstract: Protein structures are stabilized by multiple weak interactions, including the hydrophobic effect, hydrogen bonds, electrostatic effects, and van der Waals’ interactions. Among these interactions, the hydrogen bond is distinct in having its origins in electron delocalization. Recently, another type of electron delocalization, the n→π* interaction between carbonyl groups, has been shown to play a role in stabilizing protein structure. Here, we examine the interplay between hydrogen bonding and n→π* interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
146
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(152 citation statements)
references
References 33 publications
6
146
0
Order By: Relevance
“…Recently, extensive studies suggested a kind of long-range non-covalent interaction caused by electron delocalization named n → * interaction might be important for protein folding [14][15][16][17][18][19]. This interaction happens between carbonyls of peptides that the lone electrons of donor oxygen atom are delocalized over the antibonding orbital (*) of another carbonyl [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive studies suggested a kind of long-range non-covalent interaction caused by electron delocalization named n → * interaction might be important for protein folding [14][15][16][17][18][19]. This interaction happens between carbonyls of peptides that the lone electrons of donor oxygen atom are delocalized over the antibonding orbital (*) of another carbonyl [16,20].…”
Section: Introductionmentioning
confidence: 99%
“…The first lone pair participates in the NH i !C@O i-4 hydrogen bond, or n!r* interaction, leaving the second lone pair available to make an n!p* interaction with the adjacent carbonyl group. 16 Our analysis also revealed that half of carbonyl groups found in b-structure not satisfied by hydrogen bonds to water were satisfied by one backbone NH hydrogen bond (NH bb ), plus one C a -H hydrogen bond (CaH), (55%), Figure 3(A). Both of these bridge strands [ Fig.…”
Section: Types Of Nci Made Correlate With Secondary Structurementioning
confidence: 65%
“…Interestingly, when these interactions did fluctuate down to two NCI C@O in the MD simulations, it was usually one of the NH bb that was lost, and not the n!p* interaction, which perhaps runs contrary to expectations given that the latter is considered the weaker of the two interactions. 16 A third type of three-NCI C@O cluster was found in the C-terminal turns of a-helices [31 unique examples from 1039 snapshots, Fig. 4(C)].…”
Section: Types Of Nci Made Correlate With Secondary Structurementioning
confidence: 99%
See 2 more Smart Citations